Measurement of the parity-violating asymmetry parameter ab and the helicity amplitudes for the decay Lambda(0)(b) -> J/psi Lambda(0) with the ATLAS detector - Aad, G; Abajyan, T; Abbott, B; Abdallah, J; Khalek, SA; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; Abreu, H; et al. (2014)
A measurement of the parity-violating decay asymmetry parameter, αb, and the helicity amplitudes for the decay Λb0→J/ψ(μ+μ-) Λ0(pπ-) is reported. The analysis is based on 1400 Λb0 and Λ̄b0 baryons selected in 4.6fb-1 of proton-proton collision data with a center-of-mass energy of 7 TeV recorded by the ATLAS experiment at the LHC. By combining the Λb0 and Λ̄b0 samples under the assumption of CP conservation, the value of αb is measured to be 0.30±0.16(stat)±0.06(syst). This measurement provides a test of theoretical models based on perturbative QCD or heavy-quark effective theory. © 2014 CERN, for the ATLAS Collaboration.